The effect of game on students' achievement in senior secondary school physics in Oyo State (2009)
Two major problems confront the physics discipline - the problems of low enrolment and poor performance in the subject by those who eventually registered for the subject. Although, many methods were suggested by scholars to improve students' achievement in physics, not much desired effects were recorded. One of the attributes of students at any level is to play, therefore, this study examined the effects of games on students achievement in physics. The study adopted a 2 x 2 factorial design with pre-test and post-test control groups in quasi-experimental setting. Treatment was administered at two levels: (game and control). The moderator variable used in the study was gender at two levels (male and female). One hundred and twenty eight senior secondary two (S.S. 2) students in four selected secondary schools from Ibadan North and Akinyele Local Government Areas of Oyo State participated in the study. Two instruments were used: one response instrument- physics achievement test (PAT) and one stimulus instrument (teaching package). Data analysis was done using analysis of covariance (ANCOVA) with the pre-test scores serving as covariates to test for the interactive and main effects. The results indicated that there is a significant main effect of treatment on students' achievement in physics, gender also has significant effect on studnts' achievement in physics. The interaction between the treatment and gender was based on the findings, it is recommended that games should be used to complement teaching of physics.